The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/0734904113511947
|View full text |Cite
|
Sign up to set email alerts
|

Study on the pre-ignition temperature variations of wire insulation under overload conditions in microgravity by the functional simulation method

Abstract: A functional simulation method was applied to study the pre-ignition temperature variations of wire insulation under overload conditions in normal gravity. A simplified heating mode was proposed to theoretically investigate the wire heating process. Results of the temperature variations of wire insulation prior to ignition in normal gravity, but under reduced pressures, were obtained and compared with microgravity experimental results in order to investigate the effects of pressure and current on the pre-ignit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Therefore, we proposed the overload heating as the internal heat source to study the early temperature rise characteristics and radiation characteristics of wire under overload current. The experiment was performed on board the SJ-8 satellite (Kong et al 2006;Kong et al 2008;Wang et al 2014). In the experiment, there is no external ignition source, and the wire fault is caused by its own overload heating by excessive current to simulate the effects of a short circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we proposed the overload heating as the internal heat source to study the early temperature rise characteristics and radiation characteristics of wire under overload current. The experiment was performed on board the SJ-8 satellite (Kong et al 2006;Kong et al 2008;Wang et al 2014). In the experiment, there is no external ignition source, and the wire fault is caused by its own overload heating by excessive current to simulate the effects of a short circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Further on-ground studies in low pressure and narrow channel confirmed the validity of similarity theory to study the pre-ignition characteristics of wire insulations. 26,27 In drop tower, Fujita et al 28 reported the limited oxygen concentration of the PE insulation is much lower in microgravity. Guan et al 29 investigated the size and the morphology of smoke jetted from the fluorinated ethylene propylene (FEP) insulation layers before the occurrence of the flame spreading.…”
Section: Introductionmentioning
confidence: 99%